Plazma Püskürtme Yöntemiyle AISI 304 Paslanmaz Çelik Yüzeyinde Elde Edilen ZrO2 / Al2O3- % 13TiO2 Kompozit Kaplamasının Mikroyapı Özellikleri - Islak, Serkan; Buytoz, Soner (6th International Advanced Technologies Symposium (IATS’11), 16-18 May 2011, Elazığ, 2011)
In this study, ZrO2 /Al2O3 -13 % TiO2 composite coatings that various proportions of Al2O3 -13 wt. % TiO2 were reinforced into ZrO2 matrix powder were formed on the AISI 304 stainless steel surface by plasma spray. Microstructure and phase composition of coatings was determined by optical microscopy (OM), scanning electron microscopy (SEM), energy dispersive spectroscopy (EDS) and X-ray diffraction (XRD) analysis. Lamellae and porous microstructures were obtained in the coatings. In addition, a small amount of unmelted particles, partially melted and fully melted regions in microstructure of coatings were observed. With the increasing addition of Al2O3 - TiO2 , a decrease in the pores was observed. XRD analysis results showed the formation of ZrO2 , Al0.52Zr0.48O1.74, ZrTiO4 , Al0.18Zr0.82O1.91, Al2O3 , Al2Zr3 , Al3Ti and Ti2O3 phases in the coating layer. In compare to the substrate, microhardness of coating layer is 4-5 times more. Maximum
Microstructure properties of ZrO2 / Al2O3- % 13TiO2 composite coating produced with plasma spray method on AISI 304 stainless steel
Keywords: Plasma spray, ZrO2, Al2O3- 13 wt. %TiO2, microstructure